Fetichismo, ideologia e educação em Theodor Adorn - Silva, Pedro Rogério Sousa da (2016)
This paper investigated the concepts of fetishism, ideology and education in Adorno. For so, it is made a support in the theoretical and bibliographical literature and more specifically around the work and the different philosophical, sociological and educational categories of the above mentioned thinker, as well as his interlocutors and commentators. It is outlined, this way, the emergence and spread of the concept of fetishism by several authors such as Charles de Brosses, Marx, Freud and Adorno, among others. It is sketched, then Marx's point of intersection with Adorno about fetishism. It is argued, as well, fetishism in classical music and the dualism between two composers - Schoenberg and Stravinsky - as well as the musical element and their correlation with the Fetishism of Cultural Goods in Adorno, showing that the investigation of the music is a major problem which means contradiction to the Adornian thought. It is researched, moreover, the concept of beauty, showing, in a summary form, its spread in the course of the history of philosophy as well as contemporary aesthetic in Adorno, outlining some artistic currents, their impacts and purposes. We point out another appropriation of Adorno`s made against the author of Capital, namely, the concept of ideology, however, made in a divergent, and distinct way compared to the understanding of Marx. Besides that, it is analyzed the link between Adorno and Benjamin, that means, the convergences and divergences of the German philosophers about some concepts. They ascertain promptly the torment of Auschwitz, showing their origin, social and educational consequences. It is argued, moreover, how education can prevent in order to avoid that the case of Auschwitz is not repeated. It is examined, afterthought, the criticism made by Adorno to an instrumental, technical and quantitative education. Conversely, based on Adorno, it is thought to be a non-identical education at the prevailing logic, recovering the aspect of autonomy and human emancipation. They talk, finally, about the conflict between two concepts in the educational context, namely, training and semi training.